2000
DOI: 10.1063/1.593857
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mn concentration on the physical phenomena in the semimagnetic semiconductor Hg1−x−yCrxMnySe

Abstract: Results are presented from a study of the magnetic susceptibility and electron spin resonance (ESR) on Cr3+ and Mn2+ ions in a series of samples of the semimagnetic semiconductor Hg1−x−yCrxMnySe with x=0.02 and 0.01⩽y⩽0.08. The experimental results show that the structure of the ESR spectrum and the character of its shift with respect to magnetic field as the temperature changes depend on the ratio of the concentrations of chromium and manganese ions, which form two interacting substructures. The observed tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Lately, spin-glass transitions have been surprisingly observed at considerably higher temperatures (above 100 K) in several Se-based DMS of the type II 1Àx M x VI such as Hg 1Àx Cr x Se and Hg 1ÀxÀy Cr x Mn y Se [10,11]. It should be noted that the high temperature spin-glass transitions have been also reported for other Se-based materials, for example FeIn x Cr 2Àx Se 4 [12].…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Lately, spin-glass transitions have been surprisingly observed at considerably higher temperatures (above 100 K) in several Se-based DMS of the type II 1Àx M x VI such as Hg 1Àx Cr x Se and Hg 1ÀxÀy Cr x Mn y Se [10,11]. It should be noted that the high temperature spin-glass transitions have been also reported for other Se-based materials, for example FeIn x Cr 2Àx Se 4 [12].…”
mentioning
confidence: 90%
“…Our previous studies of the Hg 1Àx Cr x Se and Hg 1ÀxÀy Cr x Mn y Se crystals have shown that the later exhibits spin-glass transitions at higher temperatures, reaching the maximum value of T g and the strongest change of the magnetic susceptibility wðTÞ in the crystal composition range of x; yE0:0120:08 which is limited by the solubility of magnetic constituents in HgSe host [10,11]. In present letter, we try to explore the reason of this phenomenon by studying the magnetic susceptibility of Hg 1ÀxÀy Cr x Mn y Se crystals in dependence on their structural and compositional inhomogeneities.…”
mentioning
confidence: 98%